Poverty and Frustration as Predictor of Domestic Violence among Sandwich Students - Kamaldeen, Rahmat Tinuke; Dawodu, Muhammad Saheed; Ogo-Oluwa, Ameenat Arinola (Universitas Pendidikan Ganesha, 2023)
The prevalence of domestic violence in Nigeria remains alarmingly high, exhibiting no discernible indications of decline. Prevalence of this phenomenon is observed among couples irrespective of their age, ethnic background, religious affiliation, or socioeconomic standing. This study aims to investigate the relationship between poverty and dissatisfaction as predictors of spousal violence among sandwich students. The research employed a descriptive design of the ex-post-facto kind. A multi-stage selection procedure was employed to pick a sample of 120 respondents from three departments. The participants were assessed using appropriate standardized measures (instruments) and the collected data were subjected to statistical analysis utilizing the percentage and Pearson Product Moment Correlation (PPMC) and Multiple Regression techniques at a significance level of 0.05. Hence, in light of the research indicating a significant correlation between poverty and domestic violence, it is suggested that counseling professionals and psychologists should enhance their endeavors to organize seminars for student couples.